Electroacupuncture Therapy for Post-Stroke Speech Disorder with Yang Liver Hyperactivity Syndrome - Zaimatus Sofia; Heni Nur Kusumawati; Eka Deviany Widyawaty (HAKTI : Indonesian Acupuncture Therapists Association, 2024)
Stroke is a condition when blood flow in certain areas of the brain suddenly occurs damage to some brain cells which then experience death due to impaired blood flow due to blockage or rupture of brain blood vessels. One of the signs of symptoms arising from stroke is a speech disorder. Objective: To determine the effectiveness of electroacupuncture therapy with Tiantu points (CV 22), Lianquan (CV 23), Dicang (ST 4), Jianche (ST 6), Hegu (LI 4), Tongli (HT 5), (SP 6), Taixi (KI 3), Xingjian (LV 2), Taichong (LV 3) and additional therapy using scalp acupuncture in patients with post-stroke speech disorders. Management of post-stroke speech disorders by electroacupuncture methods at Tiantu (CV 22), Lianquan (CV 23), Dicang (ST 4), Jianche (ST 6), Hegu (LI 4), Tongli (HT 5), (SP 6), Taixi (KI 3), Xingjian (LV 2), Taichong (LV 3) and additional therapy using scalp acupuncture. The principle of therapy in this case is to strengthen Yin, calm the Heart, and improve the circulation of Qi and blood. Therapy is carried out in as many as 6 therapy sessions. The result measurement indicator uses the Barthel Index form. Electroacupuncture therapy as many as 6 therapy sessions is effective to increase the comfort of patient activities and the changes that occur are very significant.